Specificity of CD200/CD200R pathway in LPS-induced lung inflammation - Patoine, Dany; Bouchard, Karine; Lemay, Anne-Marie; Bissonnette, Elyse Y.; Lauzon-Joset, Jean-Francois (Frontiers in Immunology, 2022)
At lung mucosal sufaces, immune cells must initiate inflammatory response against pathogen without inducing tissue damage. Loss of this equilibrium can lead to acute respiratory distress syndrome (ARDS), a severe lung inflammatory disease characterized by excessive inflammation and dysregulation of anti-inflammatory pathways. To investigate the role of anti-inflammatory pathway CD200/CD200R in lung inflammatory response, we administered LPS intratracheally in CD200 KO and wild type (WT) rats. Inflammation was evaluated using bronchoalveolar lavage (BAL) cellularity. Lung injury was measured by total protein level in BAL fluid, and levels of proinflammatory cytokines (TNF, IL-6) and chemokines (CXCL2, CCL2) were determined in BAL supernatants. In a second series of experiments, recombinant CD200Fc was administered to KO rats to restore the anti-inflammatory response. At baseline, CD200 KO rats did not show sign of inflammation, however KO rats had lower number of alveolar macrophages. In addition, LPS administration induced greater pulmonary edema in CD200 KO rats. This was accompanied with a higher recruitment of neutrophils as well as levels of TNF, IL-6, CXCL2, and CCL2 in BAL compared to WT rats. CD200Fc administration in KO rats reduced neutrophil accumulation and TNF and CXCL2 levels in BAL. Interestingly, the increased inflammatory response of CD200 KO rats could be attributed to greater activation potential of alveolar macrophages with higher levels of ERK and P-ERK MAPK. In conclusion, this study shows that lung inflammatory response is exacerbated in absence of CD200 in an experimental model of ARDS in rats. In addition, CD200/CD200R pathway shows selective regulation of acute lung inflammation and cannot completely abrogate the complex LPS-induced inflammatory response. However, addition of CD200 agonist in a multi-target therapy strategy could have beneficial impacts.